Pentahelix Collaboration in Tourism Development Based on Local Wisdom in Batu City - Widodo, Surjo (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
The purpose of this study is to try to describe and analyze pentahelix collaboration in the development of tourism based on local wisdom in the post-covid pandemic improvement era. Based on Local Wisdom, Tourism Development is a flagship program in an effort to restore interest in visiting tourists after the COVID-19 pandemic in Batu City. This research was conducted using library research. This study found collaboration between actors in the pentahelix model in increasing tourism based on local wisdom, prioritizing unique forms that grow and develop in the community, natural tourism that is modified in such a way.